Learning Revolution In The Digital Age: Indonesia And America - Ika Kurnia Sofiani; Irna saputri; Salsabila Inda Rafifah (Kasyafa: Jurnal Pendidikan Agama Islam, 2025)
The digital revolution has brought fundamental changes to the global education system, including in Indonesia and the United States. The development of information technology has driven the transformation of teaching methods, access to learning resources, and interaction between teachers and students. However, this change has also brought a number of challenges, such as infrastructure inequality, unequal digital literacy, and the need to formulate integrated technology-based education policies. This study aims to examine the dynamics of the transformation of the education system in Indonesia and America, with a focus on the use of technology in learning, government policies, and their impact on the quality of education. The method used is a literature study through analysis and synthesis of various trusted sources, including government reports, scientific articles, and online publications. The discussion shows that the United States is more advanced in the integration of educational technology with the support of strong infrastructure, regulations, and a digital learning culture, while Indonesia is still in the adaptation stage with various structural barriers. Despite having different contexts, both countries face similar challenges in maintaining inclusivity, curriculum relevance, and a balance between technological innovation and humanist values ​​in education.